2018
DOI: 10.1038/s41598-018-27079-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sources and bioaccumulation pathways of MeHg in subantarctic penguins: a stable isotopic investigation

Abstract: Seabirds are widely used as bioindicators of mercury (Hg) contamination in marine ecosystems and the investigation of their foraging strategies is of key importance to better understand methylmercury (MeHg) exposure pathways and environmental sources within the different ecosystems. Here we report stable isotopic composition for both Hg mass-dependent (e.g. δ202Hg) and mass-independent (e.g. Δ199Hg) fractionation (proxies of Hg sources and transformations), carbon (δ13C, proxy of foraging habitat) and nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 66 publications
(130 reference statements)
4
39
0
Order By: Relevance
“…Δ 199 Hg/Δ 201 Hg slopes have been experimentally estimated during MeHg photodemethylation (1.36 ± 0.02) and Hg(II) photoreduction (1.00 ± 0.02) in aquatic compartments (Bergquist and Blum, 2007). The Δ 199 Hg/Δ 201 Hg ratios calculated for the tissues of the three seabird species ( Fig S2) are in line with slopes previously reported in marine organisms (Day et al, 2012;Masbou et al, 2015Perrot et al, 2016;Renedo et al, 2018aRenedo et al, , 2018b. Since Hg MIF is thought to be unaltered by Hg metabolic processes, no changes in Δ 199 Hg values were expected among seabird tissues.…”
Section: Hg Mif Values Related To Specific Ecological Characteristicssupporting
confidence: 89%
See 2 more Smart Citations
“…Δ 199 Hg/Δ 201 Hg slopes have been experimentally estimated during MeHg photodemethylation (1.36 ± 0.02) and Hg(II) photoreduction (1.00 ± 0.02) in aquatic compartments (Bergquist and Blum, 2007). The Δ 199 Hg/Δ 201 Hg ratios calculated for the tissues of the three seabird species ( Fig S2) are in line with slopes previously reported in marine organisms (Day et al, 2012;Masbou et al, 2015Perrot et al, 2016;Renedo et al, 2018aRenedo et al, , 2018b. Since Hg MIF is thought to be unaltered by Hg metabolic processes, no changes in Δ 199 Hg values were expected among seabird tissues.…”
Section: Hg Mif Values Related To Specific Ecological Characteristicssupporting
confidence: 89%
“…However, this seabird is known to migrate to warmer subtropical waters during interbreeding periods (Cherel et al, 2016) and they assimilate MeHg from different marine pools both at the breeding site (subantarctic and Antarctic during their chick-rearing period) and during their winter migration far from their colonies (subtropical). A recent study on resident seabirds showed higher (~ 0.6 ‰) blood Δ 199 Hg values in subtropical populations relative to Antarctic populations as a result of higher extent of MeHg photodemethylation at subtropical latitudes (Renedo et al, 2018b). This observation supports that the higher Δ 199 Hg values in feathers could be associated to the assimilation of more photochemically impacted MeHg from subtropical habitats during the inter-breeding period.…”
Section: The Significant Difference Of δ 199 Hg Values Between Feathementioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, Hg isotopes have been widely used in the last decades as a new and powerful perspective to explore the cycle of this element (Blum et al, 2014) and could thus be used to track the trophic and spatial origins of Hg in polar seabirds (Renedo et al, 2018). Hg has seven naturally occurring stable isotopes that undergo both mass-dependent fractionation (MDF) and mass-independent fractionation (MIF), both related to distinct Hg isotopic ratios.…”
Section: Future Direction: Spatial Ecotoxicology To Link Seabirdmentioning
confidence: 99%
“…Furthermore, deep-sea organisms have been reported to contain higher Hg concentrations relative to epipelagic animals (Chouvelon et al, 2012;Choy et al, 2017;Monteiro et al, 1996), which also contributes to an increased exposure of Hg for squids migrating towards deeper waters. Further investigations are needed to validate this hypothesis, including the use of stable isotopes of Hg (e.g., Blum et al, 2013;Renedo et al, 2018).…”
Section: Mercury and Seleniummentioning
confidence: 99%